Psicologia e ética contemporânea para o desenvolvimento do clima organizacional sustentável - Nascimento, Andréa Maria Fardin do (2011)
This text discusses the intricate inter-subjective relations that develop in the companies. It assesses the issues involved in training strategies, development and learning that arise from new approaches in the sector of administration, within companies, on the optimization and better functional performance. The perspective of organizational psychology and approaches from a bias in the ethics of care and ethic of solidary sensibility will help us evaluate ways of perceiving problems and opportunities around the organization as an area dedicated to human development and mental health workers. Considering that no job is exempt from suffering, given the pressing need to work in order to survive, and that exist for all, factors and demands, which drive people to large psychic investments, in different settings and events, many people are led to tense experiences and living rewarding in the area of administrative work. Emotions are an integral part of the organizational environment- business; they make up the backdrop of leading individuals and groups, reflecting on thought and action of each one, having to deal with certain emotional intelligence on the settings that relate to the irrational and mental exhaustion. The way work teams negotiates with emotions and interrelationship is what will really determine the scale of organizational climate. The values that establish the organizational behavior are what qualify the work climate, and on these relationships is that this research will make some contributions, in order to understand the possibilities that psychology, along with contemporary ethical values, can collaborate with inter-subjective relationship and with the organizational climate.